Towards Federated Ontology-Driven Data Integration in Continuous Software Engineering - Santos Júnior, Paulo Sérgio; Almeida, João Paulo A.; Barcellos, Monalessa (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
Organizations have adopted Continuous Software Engineering (CSE) practices aiming at making software development faster, iterative, integrated, continuous, and aligned with the business. In this context, they often use different applications (e.g., project management tools, source repositories, and quality assessment tools) that store valuable data to support daily activities and decision-making. However, data items often remain spread in different applications that adopt different data and behavioral models, posing a barrier to integrated data usage. As a consequence, data-driven software development is uncommon, missing valuable opportunities for product and process improvement. In this paper, we explore an ontology network addressing CSE aspects to develop a data integration solution in which networked ontologies are the basis to build reusable and autonomous software components that work together in a system federation to provide meaningful integrated data. We achieve a comprehensive and flexible solution that can be used as a whole or partially, by extracting only the components related to the subdomains of interest.